Scénario socio-économique et écologique des changements de l’occupation des terres au Bénin - Joseph Oloukoi (VertigO)
This study appreciates the dynamic of land cover in a faraway or middle future. It is based on a combinatory approach that integrates spatial remote sensing, geographic information system and cellular automata techniques. Landsat TM of 1986, ETM of 2000 and NigeriaSat1 of 2006 images were used for the extraction of land cover information. These information were processed and converted to ASCII format in ArcGIS and then recuperated in SPACELLE cellular automata application model, where predictions of land cover were made towards 2025 and 2034, under defined conditions. The change detection reveals a progressive trend of farm and fallow lands, shrub and woody savannah between 1986 and 2006. Dense forest and gallery forest presented a regressive trend in the four landscape units selected. The socio-economic scenario reveals that vegetation formations will almost disappear at the profit of farm and fallow lands and settlements in 2016, 2025, trend that will be consolidated in 2034. The ecological scenario has turned to an environmental stability scenario that translated into a relative dynamic of land cover units. It preserves the resources because their degree of degradation will be low.